Kepemimpinan Inovatif dan Implikasinya terhadap Pencapaian SDGs Ekonomi Berkelanjutan: Studi Langkah Strategik Ekonomi Kreatif Era Presiden Joko Widodo - Alfarizi, Muhammad; Arifian, Rafialdo (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
The 2030 Agenda for Sustainable Development aims to promote sustainable development through seventeen Sustainable Development Goals (SDGs). In response to global economic dynamics, Indonesia has developed the creative economy as a key pillar of development, with subsectors such as culinary, fashion, and crafts making significant contributions to GDP. Under the leadership of President Joko Widodo, this sector has been prioritized through innovation, digitalization, and the strengthening of MSMEs. This study aims to analyze the impact of innovative leadership determinants on the economic performance of the SDGs, utilizing a quantitative approach with primary data collected via a 5-point Likert questionnaire from 200 MSME actors within the creative economy subsector during the period of September–October 2024. The analysis is conducted using a PLS-SEM model with the assistance of SmartPLS 4 software. The findings indicate that leadership styles such as empowerment, inspirational learning, transformational, and resilient visionary leadership have a positive influence on the economic SDG performance, with a significant moderating role of democratic culture on certain leadership dimensions. This study recommends that the next national leaders continue the empowerment strategy for MSMEs through innovative, digital-based policies, enhance public participation, and foster synergy among stakeholders to accelerate the achievement of sustainable economic SDGs.